The Influence of Administrative Practices and Service Quality on Patient Loyalty Mediated by Patient Satisfaction - Agestie, Sylvia; Athalia, Rizqi; Oktariana, Thalia Puteri; Nainggolan H, Maria (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Acquiring new patients and retaining existing patients is a challenge for healthcare institutions due to competition in the healthcare industry. This study aims to analyze the influence of administrative practices and service quality on patient loyalty through patient satisfaction as the mediator. The study population was patients at Pelabuhan Hospital Palembang. A total of 156 patients became the research respondents. Purposive sampling technique was chosen as the method of obtaining the research sample. Data collection was carried out using Google Forms. Data analysis methods used were PLS SEM and importance performance map analysis. The results of the study did not indicate any influence of administrative practices on patient loyalty, but administrative practices had a positive effect on patient satisfaction. Service quality was found to have a positive effect on patient satisfaction and also patient loyalty. Patient satisfaction was found to have a positive effect on patient loyalty. Patient satisfaction fully mediated the effect of administrative practices on patient loyalty. Patient satisfaction partially mediated the effect of service quality on patient loyalty. Service quality and patient satisfaction are factors that must be considered to maintain patient loyalty. Further research can be conducted on other patients at other hospitals around Palembang, conducted longitudinally, and using a combination of qualitative and quantitative methods to enrich the research results.